A novel design of reconfigurable Fourier transform operator over (C) and GF (Ft) for future multi-standards SDR equipments. (11th May 2010) - Gul, Sufi Tabassum; Moy, Christophe; Louet, Yvet; Al Ghouwayel, Ali
Reed Solomon (RS) encoding/decoding in frequency domain is of significant interest in many wireless systems because the fast Fourier transform (FFT) operator is already present, at least in orthogonal frequency division multiplexing (OFDM) based ones. This paper presents and analyses the role of FFT to perform RS encoding/decoding in frequency domain. After explicating performance comparison, we propose to use RS codes defined over GF (Ft) instead of RS codes over GF (2m). Based on this proposition, we have developed a common dual mode fast Fourier transform (DMFFT) operator able to operate over two different domains C and GF (Ft). Various implementation strategies for DMFFT operator have been discussed. We emphasise that this DMFFT operator is a strong candidate for common operators in future air interface standards. We also explain our approach for designing flexible multi-standard radio systems. Finally, we incorporate the DMFFT operator in our graph and solve optimisation problem by a heuristic based on simulated annealing.